Exploring ecolinguistics: A new paradigm for tourism English learning - Astawa, I Gede (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study investigates the integration of ecolinguistic principles into English language instruction for tourism students to enhance their environmental awareness and communication skills. Employing a qualitative approach, the research involved 29 tourism students at the Denpasar Academy of Tourism in Indonesia. Data were gathered through a practical adventure tour activity and individual interviews. The findings reveal that ecolinguistic strategies significantly improved students’ use of environment-related vocabulary, increased their confidence in discussing ecological issues in English, and cultivated a stronger sense of environmental responsibility. The study suggests that embedding ecolinguistics in English tourism education equips future professionals with the linguistic tools to promote sustainability in the tourism industry.